2014
DOI: 10.3389/feart.2014.00012
|View full text |Cite
|
Sign up to set email alerts
|

Satellite radar data reveal short-term pre-explosive displacements and a complex conduit system at Volcán de Colima, Mexico

Abstract: The geometry of the volcanic conduit is a main parameter controlling the dynamics and the style of volcanic eruptions and their precursors, but also one of the main unknowns. Pre-eruptive signals that originate in the upper conduit region include seismicity and deformation of different types and scales. However, the locality of the source of these signals and thus the conduit geometry often remain unconstrained at steep sloped and explosive volcanoes due to the sparse instrumental coverage in the summit region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 51 publications
3
47
0
Order By: Relevance
“…As this system continues to "unzip," these intrusions and subsequent vent openings could facilitate future slope movement to the SW. Geomechanical studies have found that continued dike intrusions have the possibility of imparting mechanical damage to the rock [45], leading to edifice weakening and a higher probability of slope instability. Additionally, if several pathways bleed the main conduit, the lack of localized accumulation of degassed magma may not cause deformation measurable above InSAR detection limits until magma reaches the surface [46], such as the diking event near the 2010 vents (Figure 5a). This could account for a lack of measurable inflation due to magma intrusion into the cone prior to the 2010 eruptions (Figure 3a, [22]).…”
Section: Lava Flow Emplacement and Subsidencementioning
confidence: 99%
“…As this system continues to "unzip," these intrusions and subsequent vent openings could facilitate future slope movement to the SW. Geomechanical studies have found that continued dike intrusions have the possibility of imparting mechanical damage to the rock [45], leading to edifice weakening and a higher probability of slope instability. Additionally, if several pathways bleed the main conduit, the lack of localized accumulation of degassed magma may not cause deformation measurable above InSAR detection limits until magma reaches the surface [46], such as the diking event near the 2010 vents (Figure 5a). This could account for a lack of measurable inflation due to magma intrusion into the cone prior to the 2010 eruptions (Figure 3a, [22]).…”
Section: Lava Flow Emplacement and Subsidencementioning
confidence: 99%
“…Álvarez and Yustis () also used gravity data to infer evidence for the southward migration of the volcanic front in CVC, which was previously proposed by Luhr and Carmichael () based on geological and petrological data. Ground deformations during recent eruption episodes were studied using satellite radar measurements (Salzer et al, ) and provided some information about the shapes and depths of active magma reservoirs. More information about the processes in the plumbing system beneath CVC was obtained based on the analysis of focal mechanisms of seismic events recorded by permanent stations (Núnez‐Cornú & Sánchez‐Mora, ).…”
Section: Introductionmentioning
confidence: 99%
“…A noteworthy example of the value in SAR data for tracking lava dome growth is that of Merapi, Indonesia, in 2010, where amplitude imagery aided in the recognition of rapid dome growth and assessment of collapse potential despite persistent cloud cover that obscured other types of observations (especially at visible wavelengths) [ Pallister et al ., ]. Tracking dome growth and deformation (both of the dome and surrounding terrain) is critical for hazards assessment because dome growth rate has been tied to explosive potential [e.g., Pallister et al ., ], and localized transient deformation has been shown to immediately precede explosions at some dome‐building volcanoes [e.g., Salzer et al ., ].…”
Section: Introductionmentioning
confidence: 99%